Aerodynamic drag in field cycling with special reference to the Obree's position - Grappe, F.; Candau, R.; Belli, A.; Rouillon, J. D. (Ergonomics, 1997)
In cycling at race speeds, 90% of total resistance opposing motion, RT(N) T depends on aerodynamic drag of air, which is directly proportional to the effective frontal area, ACd(m2). RT was measured on a cyclist, in an open velodrome, in order to evaluate ACd in four different positions on a traditional bicycle: upright d position (UP), dropped position (DP), aero position (AP) and Obree's position (OP : the hands in support under the chest, the forearms tucked on the arms, the trunk tilted forward). RT was determined at different constant speeds, Vc(m s-1) with a special device (Max One), which allows the measurement of the external mechanical power Pext(W) in real conditions of cycling locomotion ext (RT = PextVc-1). Experiments were carried out in order to test the validity and the reproducibility of Pext provided by the measurement device. Pext was measured twice in the same experimental conditions (exercise on a treadmill against slopes varying from 1 to 14%) and no significant difference was observed between the two measurement series. A systematic measurement error was observed allowing the use of a correcting factor. As expected, in the four rider positions, RT increased linearly (p<0.001, r = 0.90-0.95) with Vc2. ACd were significantly different (p<0.001) between the four positions, except between DP and AP. As compared to UP, in DP, AP and OP the significant reductions of ACd were 7.8, 12.4 and 27.8%, respectively. These reductions were associated with the degree of rachis flexion and with the decrease of the lateral distance between the two upper limbs. In UP, ACd (0.299 m2) was lower (-23%) than those reported in previous studies. In DP and AP, ACd (0.276 m2 and 0.262 m2, respectively) were similar to those reported in previous studies. In OP, no study allowed a real comparison with the value of ACd (0.216 m2) found in this study. The average rolling resistance (Rr = 1.95±0.81 N) determined according to the four positions was in line with previous reports. These findings suggest that the position adopted by Obree significantly reduces the aerodynamic drag and, thus, is an important factor in cycling performance.